2016
DOI: 10.4070/kcj.2016.46.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan 160 mg/Amlodipine 5 mg Combination Therapy versus Amlodipine 10 mg in Hypertensive Patients with Inadequate Response to Amlodipine 5 mg Monotherapy

Abstract: Background and ObjectivesWhen monotherapy is inadequate for blood pressure control, the next step is either to continue monotherapy in increased doses or to add another antihypertensive agent. However, direct comparison of double-dose monotherapy versus combination therapy has rarely been done. The objective of this study is to compare 10 mg of amlodipine with an amlodipine/valsartan 5/160 mg combination in patients whose blood pressure control is inadequate with amlodipine 5 mg.Subjects and MethodsThis study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
3
8
1
2
Order By: Relevance
“…In a clinical trial that compared racemic amlodipine plus TEL combination versus TEL monotherapy, the overall incidence rate of AEs was 22.2% to 34.5% in the TEL monotherapy group compared with 30.1% to 37.5% in the racemic amlodipine plus TEL combination group, but the difference was not significant between the groups. [12][13][14][15] In the present study, the overall incidence rate of AEs in the TEL 80-mg group was similar to those in the previous study, but the rates (approximately 20%) in the S-AM/TEL groups were relatively lower than the incidence rate in the previous study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In a clinical trial that compared racemic amlodipine plus TEL combination versus TEL monotherapy, the overall incidence rate of AEs was 22.2% to 34.5% in the TEL monotherapy group compared with 30.1% to 37.5% in the racemic amlodipine plus TEL combination group, but the difference was not significant between the groups. [12][13][14][15] In the present study, the overall incidence rate of AEs in the TEL 80-mg group was similar to those in the previous study, but the rates (approximately 20%) in the S-AM/TEL groups were relatively lower than the incidence rate in the previous study.…”
Section: Discussionsupporting
confidence: 84%
“…13,14 However, the rate was 1.4% to 5.1% and 3.6% to 7.0% with racemic amlodipine/ TEL 5/40 mg and 10/40 mg, respectively, indicating that increasing the dose of amlodipine did not result in a great increase in the occurrence rate of edema as was with the monotherapy. [11][12][13][14][15] In the present study, edema was observed in 1 person each (approximately 1.7%) in the S-AM/TEL 2.5/40-mg group and S-AM/ TEL 5/40-mg group, supporting that increasing the dose of S-AM (2.5 to 5 mg) does not result in a higher incidence rate of edema. Furthermore, the rate of edema in the S-AM/TEL 5/40-mg group was relatively lower than the rate with racemic amlodipine 10-mg monotherapy (17% to 27.2%) and even lower than the rate with racemic amlodipine/TEL 10/40-mg combination therapy (3.6% to 7.0%).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, dose-dependent adverse effects of amlodipine, such as ankle edema, can be reduced by combining it with an ARB. 28,29 Chlorthalidone affects the distal convoluted tubule of the nephron, producing diuretic effects. Although head-to-head comparisons of cardiovascular outcomes between chlorthalidone and hydrochlorothiazide have not been conducted, a few studies have suggested that chlorthalidone has superior efficacy compared with that of hydrochlorothiazide.…”
Section: Discussionmentioning
confidence: 99%
“…Sung и соавт. [21] проводили сравнительный анализ антигипертензивной эффективности и безопасности ФК В/А в дозе 160/5 мг и монотерапии амлодипином в дозе 10 мг у 221 пациента с АГ (средний возраст 54±11 лет). Период наблюдения после рандомизации составлял 8 нед, по его завершению вновь повторяли СМАД.…”
Section: Discussionunclassified